APLIKASI DETEKSI PSIKOLOGI ANAK USIA 12 – 15 TAHUN DI SMP BETHEL TASIKMALAYA - Nugraha, Agus Ramdhani (LPPM STMIK DCI, 2013)
In this era when everything is expected to be instant, especially in field of Information Technology (IT), people are trying to find the quickest and easiest way to get the best solution, for examples are analysis, data processing, etc. Therefore, the progress of computer technology and its development should be able to meet the needs of everyone. It includes the possibility to detect the psychology of an individual. That is why the making of